HISTORICAL IMAGE IN UZBEK LITERATURE AND WAYS OF ITS EXPRESSION (Scientific journal of the Fergana State University, 2024)
This article analyzes the plot, composition, stanza system, ways and means of expressing the epic of Muhammad Ali “Mashrab”, highlights the artistic skill of the poet. This epic tells about the young Baborahim Mashrab, who goes from Namangan to Kashgar – to the famous Eshon Afakhoji gorge, falls in love with gulgun, who is mocked at a feast, and Eshon Afakhoji expels Mashrab from the gorge, severely punishing him, and then with a gang of kalandars arrives in Balkh and in anger Mahmudbi drags him to the gallows. Consisting of eight lines, two are divided into songs, each of which is devoted to the analysis of the epic, consisting of forty-five stanzas.